A model of optimal protein allocation during phototrophic growth - Faizi, Marjan; Zavřel, Tomáš; Loureiro, Cristina; Červený, Jan; Steuer, Ralf (Biosystems, 2018)
Photoautotrophic growth depends upon an optimal allocation of finite cellular resources to diverse intracellular processes. Commitment of a certain mass fraction of the proteome to a specific cellular function typically reduces the proteome available for other cellular functions. Here, we develop a semi-quantitative kinetic model of cyanobacterial phototrophic growth to describe such trade-offs of cellular protein allocation. The model is based on coarse-grained descriptions of key cellular processes, in particular carbon uptake, metabolism, photosynthesis, and protein translation. The model is parameterized using literature data and experimentally obtained growth curves. Of particular interest are the resulting cyanobacterial growth laws as fundamental characteristics of cellular growth. We show that the model gives rise to similar growth laws as observed for heterotrophic organisms, with several important differences due to the distinction between light energy and carbon uptake. We discuss recent experimental data supporting the model results and show that coarse-grained growth models have implications for our understanding of the limits of phototrophic growth and bridge a gap between molecular physiology and ecology.
Keywords: Phototrophic Processes; bakteriální proteiny; Cell Enlargement; Synechococcus; fototrofní procesy; biologické modely; Cyanobacteria; Bacterial Proteins; zvětšování buněk; sinice; Models, Biological